2020
DOI: 10.3389/fnins.2020.00757
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Music Intervention on Attention in Children: Experimental Evidence

Abstract: Although music has been utilized as a therapeutic tool for children with cognitive impairments, how it improves children's cognitive function remains poorly understood. As a first step toward understanding music's effectiveness and as a means of assessing cognitive function improvement, we focused on attention, which plays an important role in cognitive development, and examined the effect of a music intervention on children's attention. Thirty-five children, aged 6 to 9 years, participated in this study, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…According to Winner et al 8 , music learning results in neurological, cognitive, social, and motivational activation, which are areas other than music. A recent study showed that a 30-min intervention of interactively playing music on a musical instrument improved children’s control over attention more than playing video games for the same amount of time 30 . Considering this recent finding, the experience in a music club (i.e., a brass band or choir) may have a similar impact on adolescents, resulting in higher academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…According to Winner et al 8 , music learning results in neurological, cognitive, social, and motivational activation, which are areas other than music. A recent study showed that a 30-min intervention of interactively playing music on a musical instrument improved children’s control over attention more than playing video games for the same amount of time 30 . Considering this recent finding, the experience in a music club (i.e., a brass band or choir) may have a similar impact on adolescents, resulting in higher academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…After finishing, they were assigned randomly to either the MAVG or control game group for the intervention session after a short break. Both groups’ participants completed post-intervention ANT 10 min after the intervention in order to minimize any transient effect of heightened arousal levels ( Kasuya-Ueba, Zhao & Toichi, 2020 ; Yu et al, 2020 ; Ishihara et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, Pratt et al (1995) demonstrated that background music reduced hyperactive behavior in individuals with ADHD, while Jackson (2003) showcased that music can improve cognitive processes and sensory integration in children with ADHD, as well as that music therapists address these children’s symptoms from multidisciplinary perspectives. Further, Kasuya-Ueba et al (2020) concluded that music therapy has only a short-term effect on attentional control in children. Despite these reports on the positive effects of music interventions on children with ADHD, they also encompass limitations, which are mostly related to their focus: it was placed more on the effects of music interventions on attention and hyperactivity/impulsivity in ADHD and less on the effects on children with ODD.…”
Section: Introductionmentioning
confidence: 99%